The Role of Troponin in Blunt Cardiac Injury After Multiple Trauma in Humans - Kalbitz, Miriam; Pressmar, Jochen; Stecher, Johanna; Weber, Birte; Weiss, Manfred; Schwarz, Stephan; Miltner, Erich; Gebhard, Florian; Huber-Lang, Markus (World Journal of Surgery, 2017)
Background: The incidence of cardiac injury in immediate fatalities after blunt trauma remains underestimated, and reliable diagnostic strategies are still missing. Furthermore, clinical data concerning heart-specific troponin serum levels, injury severity score (ISS), catecholamine treatment and survival of patients on admission to the hospital have rarely been interrelated so far. Therefore, the object of the present study was to identify predictive parameters for mortality in the context of blunt cardiac injury. Methods: This retrospective observational study included 173 severely injured patients with an ISS ≥25 admitted to the University Hospital of Ulm, a level 1 trauma center, during 2009–2013. Furthermore, 83 blunt trauma victims who died before hospital admission were subjected to postmortem examination at the Institute of Legal Medicine, University of Ulm, during 2009–2014. ISS, cardiac injury and associated thoracic injuries were determined in both groups. Furthermore, in the hospitalized patients, serum troponin and IL-6 levels were measured. Results: Macroscopic heart injury was observed in 18 % of the patients who died at the scene and only in 1 % of the patients admitted to the hospital, indicating that macroscopic heart injury is associated with an immediate life-threatening condition. Troponin levels were elevated in 43 % of the patients after admission to the hospital. Moreover, troponin serum concentrations were significantly higher in patients treated with norepinephrine (26.4 ± 4 ng/l) and in non-survivors (84.9 ± 22.8 ng/l) compared to patients without catecholamines and survivors, respectively. Conclusions: Macroscopic heart injury was 20 times more frequent in non-survivors than in survivors. Serum troponin levels correlated with mortality after multiple injury and therefore may represent a valuable prognostic marker in trauma patients.
CRIS-Team Scopus Importer:2020-12-21